2019
DOI: 10.2147/idr.s222943
|View full text |Cite
|
Sign up to set email alerts
|

<p>Resistance To First-Line Antituberculosis Drugs And Prevalence Of <em>pncA</em> Mutations In Clinical Isolates Of <em>Mycobacterium tuberculosis</em> From Zunyi, Guizhou Province Of China</p>

Abstract: BackgroundChina is one of the high-burden countries for multidrug-resistant tuberculosis (MDR-TB), and pyrazinamide is one of the anti-TB drugs used for the shorter MDR-TB treatment regimen. The aim of this study was to determine the correlation between pncA gene mutations and resistance to four first-line anti-TB drugs as well as treatment history in clinical isolates of Mycobacterium tuberculosis.Patients and methodsM. tuberculosis clinical isolates were collected from 318 in-patients with smear-positive TB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…This result was in line with a study conducted in Belarus, Iran, which showed that the most common age group found in patients with first-line OAT resistance was the 25-44 year age group with 318 patients (34%) (Surkova et al, 2012). This result was also under a study by Cao et al (2019) in China, which showed that patients with the highest number of first-line Anti-TB drugs resistance were 35-55 years with 72 patients (39%). Based on the explanation above, it could be seen that the highest age group was found in the working-age group.…”
Section: Characteristics Of Drug-resistant Tb Patientssupporting
confidence: 88%
“…This result was in line with a study conducted in Belarus, Iran, which showed that the most common age group found in patients with first-line OAT resistance was the 25-44 year age group with 318 patients (34%) (Surkova et al, 2012). This result was also under a study by Cao et al (2019) in China, which showed that patients with the highest number of first-line Anti-TB drugs resistance were 35-55 years with 72 patients (39%). Based on the explanation above, it could be seen that the highest age group was found in the working-age group.…”
Section: Characteristics Of Drug-resistant Tb Patientssupporting
confidence: 88%
“…Although preventable and treatable, with 1.5 million deaths every year, TB is still on the world’s top list of infectious killer diseases [ 1 ]. Furthermore, with the advent of multidrug-resistant tuberculosis (MDR-TB), first-line drugs have been rendered ineffective [ 2 , 3 ]. An estimated 10 million active TB cases were recorded in 2020, which consisted of 5.6 million men, 3.3 million women, and 1.1 million children [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study analyzed the epidemiology of drug-resistant TB in seven rural areas in Hangzhou (Yuhang, Fuyang, Linan, Tonglu, Jiande, Chunan, and Xiaoshan). Of all included patients, 76.96% (1 984/2578) were Hangzhou residents, and the proportion of previously treated patients was 25.02% (645/2 578), which was significantly lower than the data from other TB hospitals in China 8 . The results indicated a functioning local TB control program in Hangzhou, China.…”
mentioning
confidence: 58%